Case Report: A case of perirectal abscess complicated with rectal necrosis - Xu, Yingfeng; Wang, Zhiting; Hu, Jianwen; Xie, Jiajia; Chen, Shiwei; Ke, Ke (Frontiers in Surgery, 2025)
Rectal necrosis represents the extreme progression of ischemic proctitis. Given the unique blood supply of the rectum, which features an extensive collateral circulation, cases of rectal necrosis are extremely rare, accounting for 2%–5% of the ischemic colitis cases. The etiology and pathogenesis of rectal necrosis encompass acute vascular occlusion, severe vascular diseases, low blood flow states, and factors such as radiotherapy, vasculitis, and mesenteric venous myointimal hyperplasia. Herein, we report a rare case of perirectal abscess complicated by rectal necrosis at the Anorectal Surgery Department of Bao'an Traditional Chinese Medicine Hospital in Shenzhen. The patient underwent a one-stage incision and drainage for a rectal abscess, followed by sigmoid colostomy and a two-stage reversal of the sigmoid colostomy; all procedures were performed through multidisciplinary collaboration. The surgical outcome was favorable after a 6-month follow-up.